FACTORS RELATED TO ASSESSMENT OF MOM'S SELF-EFFICACY IN CARING FOR CHILDREN WITH DISABILITIES IN SLB PELITA NUSA PEKANBARU - Mira Agusthia; Ranti Purnama Sari; Rachmawaty M Noer (Bajang Institute, 2021)
WHO predicts an increase in people with disabilities in Indonesia every year. Data from SLBPelita Nusa obtained 35 students with disabilities. The purpose of this study was to determine the factors that influence maternal self-efficacy in caring for children with disabilities in SLB Pelita Nusa Pekanbaru in 2020.This research is analytic with cross sectional design. The sampling technique used total sampling with a sample size of 35 respondents. Data were collected using a questionnaire, then the data was analyzed univariate and bivariate analysis using the chi-square test.The results of the study found that the mother's self-efficacy in caring for children was found that almost half of the respondents as many as 20 people (57.1%) were in the high category. The frequency distribution of respondents in the aspect of cultural factors was found to be more than half of the respondents as many as 25 people (71.4%) were positive. The frequency distribution of respondents in the aspect of family support was found that more than half of the respondents as many as 23 people (67.7%) were not good. The frequency distribution of respondents in the aspect of trait factors was found that almost all respondents as many as 30 people (85.7%) were positive. The frequency distribution of respondents in the aspect of the information factor was found that almost all respondents as many as 25 people (71.4%) were positive. There is a cultural relationship p = 0.047 (p<0.05), family support is p = 0.026 (p <0.05), traits are p = 0.093 (p> 0.05) and information is p = 0.007 (p < 0.05).Based on the research results, it was found that the factor that had a high value was 85.7% of the nature of the task at hand. It is hoped that the results of this research can be used as information material for mothers, especially for mothers in caring for children with intellectual disabilities so that mothers are better able to assess their abilities in caring for children with intellectual disabilities.